Temperature- and concentration-dependent hydrogen diffusivity in palladium from statistically-averaged molecular dynamics simulations. (May 2018) - Zhou, X.W.; Heo, T.W.; Wood, B.C.; Stavila, V.; Kang, S.; Allendorf, M.D.
Abstract: Solid-state hydrogen storage materials undergo complex phase transformations in which kinetics are often limited by hydrogen diffusion that significantly changes during hydrogen uptake and release. Here we perform robust statistically-averaged molecular dynamics simulations to obtain a well-converged analytical expression for hydrogen diffusivity in bulk palladium that is valid throughout all stages of the reaction. Our studies confirm the experimentally observed dependence of the diffusivity on concentration and temperature and elucidate the underlying physics. Whereas at low hydrogen concentrations, a single dilute hopping barrier dominates, at high hydrogen concentrations, diffusion exhibits multiple hopping barriers corresponding to hydrogen-rich and hydrogen-poor local environments. Graphical abstract: Statistically averaged molecular dynamics simulations give well converged diffusive properties of hydrogen in palladium, revealing nonlinear Arrhenius behavior when hydrogen diffusion occurs in hydrogen-rich environments. Unlabelled Image